Indications, Surgical Complications, and Long-Term Outcomes in Pediatric Esophageal Reconstructions with Pedicled Jejunal Interposition Graft - Koivusalo, Antti; Suominen, Janne; Salminen, Jukka; Pakarinen, Mikko (European Journal of Pediatric Surgery, 2020)
Introduction Several surgical techniques are available for pediatric esophageal reconstruction. We started to use pedicled jejunum interposition graft (PJIG) because other techniques had significant long-term complications. In this retrospective study, the indications, surgical complications, and long-term outcomes were assessed in patients with PJIG.Materials and Methods With ethical consent, we reviewed the hospital records of 14 patients (7 females) who from 2005 to 2019 underwent a total of 16 esophageal reconstructions with PJIG.Results Median age at PJIG was 1.6 (range: 0.2–15) years. Underlying conditions were esophageal atresia (EA) (n = 11) or native esophagus lost by trauma or infection (n = 3). Eight patients with EA underwent PJIG as primary reconstruction and three as a rescue operation after complications in primary repair. Significant surgical complications occurred in 43% of patients. Major reoperations in six (43%) patients included resection and reanastomosis of strictured proximal PJIG (n = 1) and redo PJIG after failure of the first operation (n = 2). Surgical mortality was nil. After a median follow-up of 6.5 (range: 0.7–14) years, 13 (93%) patients survived, and 1 died of congenital heart disease. PJIG failed in three (23%) survivors of whom two underwent graft removal because of life-threatening aspiration and one did not start oral feeds at all. Ten survivors (77%) have full enteral feeds. Respiratory function in the survivors is satisfactory. Two patients have moderate and three mild gastroesophageal reflux symptoms.Conclusion PJIG was a functional option for a variety of conditions that required esophageal reconstruction. However, significant early and late complications required major surgical revisions.
Keywords: esophageal reconstruction; jejunal interposition; surgical complications; long-term outcomes